If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -17 = -4x + 7 Reorder the terms: -17 + -6x = -4x + 7 Reorder the terms: -17 + -6x = 7 + -4x Solving -17 + -6x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -17 + -6x + 4x = 7 + -4x + 4x Combine like terms: -6x + 4x = -2x -17 + -2x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 -17 + -2x = 7 + 0 -17 + -2x = 7 Add '17' to each side of the equation. -17 + 17 + -2x = 7 + 17 Combine like terms: -17 + 17 = 0 0 + -2x = 7 + 17 -2x = 7 + 17 Combine like terms: 7 + 17 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 8(x+2)=3x+5 | | -11*3=15+-6*3 | | 7.8p-18=2.6p-5 | | 3x+8x-40=48 | | 9(x-5)=8(x-1) | | -96+5x=-8x+86 | | 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 | | 9-x=x | | 2(x-4)+4x=10 | | -x+-3=7 | | .75v-6=.75v-6 | | 2x2=3 | | 6(c+9)=5c-1 | | 4=0.33(b+2) | | 7(x-1)+5=6-8x+7 | | 5x+3x=7x+2 | | 9x-5=3x-59 | | 21+2=24 | | 6x+9y=72 | | 4(y-9)=(y+21) | | 5(x-6)=9(2x+1) | | 6x+9=4x+13 | | 4x-(2x-3)=14 | | 0.6(x+100)+0.4x=85 | | 4s+2s-6=6 |